Infection‐driven activation of transglutaminase 2 boosts glucose uptake and hexosamine biosynthesis in epithelial cells. (5th March 2020) - Maffei, Benoit; Laverrière, Marc; Wu, Yongzheng; Triboulet, Sébastien; Perrinet, Stéphanie; Duchateau, Magalie; Matondo, Mariette; Hollis, Robert L; Gourley, Charlie; Rupp, Jan; Keillor, Jeffrey W; Subtil, Agathe
Abstract: Transglutaminase 2 (TG2) is a ubiquitously expressed enzyme with transamidating activity. We report here that both expression and activity of TG2 are enhanced in mammalian epithelial cells infected with the obligate intracellular bacteria Chlamydia trachomatis . Genetic or pharmacological inhibition of TG2 impairs bacterial development. We show that TG2 increases glucose import by up‐regulating the transcription of the glucose transporter genes GLUT‐1 and GLUT‐3 . Furthermore, TG2 activation drives one specific glucose‐dependent pathway in the host, i.e., hexosamine biosynthesis. Mechanistically, we identify the glucosamine:fructose‐6‐phosphate amidotransferase (GFPT) among the substrates of TG2. GFPT modification by TG2 increases its enzymatic activity, resulting in higher levels of UDP‐N‐acetylglucosamine biosynthesis and protein O‐GlcNAcylation. The correlation between TG2 transamidating activity and O‐GlcNAcylation is disrupted in infected cells because host hexosamine biosynthesis is being exploited by the bacteria, in particular to assist their division. In conclusion, our work establishes TG2 as a key player in controlling glucose‐derived metabolic pathways in mammalian cells, themselves hijacked by C. trachomatis to sustain their own metabolic needs. Synopsis: Increased expression and activation of transglutaminase 2 (TG2) in mammalian cells have been associated with inflammatory diseases, but the role of TG2 in pathogen defence response is ill‐defined. Here, Chlamydia trachomatis is found to induce transglutaminase 2‐mediated protein transamidation in infected cells to rewire host's glucose metabolism and sustain bacterial growth. Infection by Chlamydia trachomatis activates host transglutaminase 2 (TG2), which is required for optimal bacterial growth. TG2 regulates glucose import by controlling the transcription of glucose transporter genes. TG2 transamidates and thereby activates glucosamine fructose‐6‐phosphate amidotransferase (GFPT), leading to increased hexosamine biosynthesis in the host cell. C. trachomatis highjacks the host hexosamine biosynthesis pathway to sustain its own growth. Abstract : Chlamydia trachomatis induces transglutaminase 2‐mediated protein transamidation in infected cells to rewire host cell glucose metabolism and sustain bacterial growth.